Koroščev državnopravni koncept v ustanovni dobi Kraljevine SHS - Rahten, Andrej (Studia Historica Slovenica, 2021)
The article presents staindpoints of the leading Slovene politician Anton Korošec in the founding era of the Kingdom of Serbs, Croats and Slovenes. Based on the archival sources, press reports and memoirs, it deals with the views of Korošec regarding main problems in adopting the constitution of the new state. During the process of pass- ing the constitution of the SHS-Kingdom Korošec had to admit defeat in materialising his constitutional concepts.
Keywords: Anton Korošec; centralism; centralizem; federalism; federalizem; Kingdom of Serbs, Croats and Slovenes; Korošec, Anton; Kraljevina Srbov, Hrvatov in Slovencev; politična zgodovina; Vidovdan Constitution; Vidovdanska ustava